Role of days postdelivery on breast milk production: a secondary analysis from the EMPOWER trial - Elizabeth V. Asztalos; Alex Kiss; Orlando P. daSilva; Marsha Campbell-Yeo; Shinya Ito; David Knoppert; EMPOWER Study Collaborative Group (BMC, 2019)
Abstract Background With an increasing demand for mother's own milk to be viewed as a primary source of nutritional support in the care of very small and preterm infants, mothers of preterm infants may be at risk of expressing suboptimal amounts of milk. The use of a galactogogue is often considered when these mothers are still having challenges in breast milk production. Methods For this analysis, the study participants were the 90 mothers who participated in the EMPOWER trial and, at the time of randomization, were stratified by days post-delivery, 8-14 days and 15-21 days. The primary outcome measure was the proportion of mothers in each of the days post-delivery groups who achieved a 50% increase in breast milk volume on day 14 of the study treatment period. Results There was no significant difference in the proportion of mothers in the 8-14 days group (75.0%) who achieved a 50% increase in breast milk volume on day 14 of the study treatment period. compared to those in the 15-21 days group (60.9%), OR 1.93 (95% CI 0.78, 4.76; p = 0.15). Because comorbidities and exposure to antenatal corticosteroids between the groups of mothers were viewed as potential confounders, a logistic regression was performed after controlling for these two variables with the adjusted OR being 1.84 (0.73, 4.64; p = 0.19). Conclusions This secondary analysis was able to demonstrate that mothers of very preterm infants, < 30 weeks gestation at birth, were able to respond to the study treatment in a similar fashion regardless of timing of entry and exposure to domperidone. In the presence of a suboptimal breast milk production by the end of the first week postpartum, below 250 ml/kg/d based on infant birth weight, a 14 day treatment of domperidone could be considered to augment breast milk production. Trial registration EMPOWER has been registered at http://www.clinicaltrials.gov (identifier NCT 01512225) on January 10, 2012.